Gender equity and discrimination in Iran: an autoethnography study - Shahsavari, Vajiheh (My University, 2024)
Gender equity and discrimination in Iran represent a multifaceted and deeply entrenched set of challenges, shaping the lives of women across legal, social, and cultural spheres. This thesis provides an overview of the prevailing conditions, challenges, and resistance efforts within Iran's societal fabric. It focuses on the oppressive legal frameworks, individual narratives, and systemic injustices that perpetuate gender inequality. Iranian women are subjected to a complex web of discriminatory laws and societal norms that systematically deprive them of autonomy and basic freedoms, exemplified by mandated hijab laws and gender-biased legal practices. Individual narratives, explored through autoethnographic methods, reveal the profound impact of these inequities on women's lives, from defiance against oppressive regimes to experiences of domestic violence and sexual assault. Highlighting the resilience of women, this thesis examines various forms of resistance, including mass mobilization and global solidarity campaigns, showcasing the power of collective action in challenging and advocating for change.
Keywords: Gender equity; Discrimination; Iran; Autoethnography